Collection, characterization, conservation and utilization of Cordia sinensis Lam.: An underexploited multipurpose fruit species of hot arid regions. Issue 6 (2nd December 2020) - Dev, Rahul; Sureshkumar, M.; Kumar, Sushil; Venkatesan, K.; Singh, Traloki; Tetarwal, Arvind Singh; Patidar, Anil; Dayal, Devi; Meghwal, P. R.
Abstract: Cordia sinensis, locally known as 'Goondi' in India, is an underexploited multipurpose fruit species found in hot arid regions that is well adapted to drought, salt and hot conditions. The present study was undertaken to collect fruit samples from different locations in the Kachchh region of Gujarat, India, and to determine their field establishment for characterization, conservation and utilization. The maximum distribution of the species was observed in Bhuj (45%) and Mandvi (25%). Field boundaries (35%) and scrub forests (30%) had greater frequencies, whereas backyards had rarer frequencies (10%). The species most commonly occurred on levelled topography (60%) with a soil pH in the range of 8–8.5 (63%). Morphological data of three-year-old plants in the field gene bank showed a maximum coefficient of variation in the number of leaves per plant (66.6), followed by the number of branches per plant (45.62) and collar diameter (27.69). Wide variations were recorded in plant height (121.67–212 cm), spread (118–223 cm 2 ) and the number of branches per plant (6–24.33). Specific accessions were identified for fodder (CBCG-12, CBCG-13 and CBCG-16), early flowering and fruiting (CBCG-12, CBCG-13 and CBCG-14), easier propagation by seeds (CBCG-12 and CBCG-13) and salt tolerance (CBCG-15 and CBCG-16). Preliminary findings and information provided about this species' utilization and other aspects might be useful for future research on its domestication, sole plantation and conservation aspects, improving the exploitation of this species by present and future generations.